Terpenoid Components from Branches and Leaves of Aglaia lawii and their Biological Properties - Li, Zhi-Xuan; Huang, Dan-Yu; Li, Yang; Xian, Yan-Ying; Zheng, Hao; Tian, Yun-Cai; Tian, Yong; Zhang, Wen-Huan; Lin, Li-Gen; Gan, Li-She (Natural Products Journal, The, 2024)
Introduction: Phytochemical investigation on the twigs and leaves of Aglaia lawii (Wight) C. J. Saldanha led to the isolation and characterization of sixteen compounds, including five sesquiterpenoids (1-5), one terpenoidal macrolide (6), seven phenolic compounds (7-13), two triterpenoids (14-15), and one steroid (16). Method: Their structures were identified by spectroscopic analyses and comparison with the literature data. Eight out of the sixteen compounds were discovered from the genus Aglaia for the first time. Result: The sesquiterpenoids (1-5) may serve as important chemotaxonomic markers. In vitro, bioassays on the anti-inflammatory and anti-diabetic activities of compounds 1128;’6 were accomplished. Conclusion: Ozoroalide (6) could significantly inhibit LPS-stimulated NO production in RAW264.7 macrophages at 40 μM and caryolane-1,9β-diol (5) could largely increase the glucose uptake capacity of C2C12 cells under insulin stimulation.
Keywords: insulin